Are tag clouds useful for navigation? A network-theoretic analysis. Issue 1 (11th November 2011) - Helic, Denis; Trattner, Christoph; Strohmaier, Markus; Andrews, Keith
It is a widely held belief among designers of social tagging systems that tag clouds represent a useful tool for navigation. This is evident in the increasing number of tagging systems offering tag clouds, which hints towards an implicit assumption that tag clouds support efficient navigation. In this paper, we test this assumption from a network-theoretic perspective, and show that in many cases, it does not hold. We first model navigation in tagging systems and then simulate the navigation process in such a graph. We analyse the navigability of three tagging datasets with regard to different user interface restrictions imposed by tag clouds. Our results confirm that tag clouds have efficient navigation properties in theory, but they also show that popular user interface decisions, such as 'pagination' significantly impair their navigability. Finally, we identify a number of avenues for further research and the design of novel tag cloud construction algorithms.